Persepsi Peserta Didik terhadap Implementasi Media Nearpod pada Pembelajaran Pendidikan Pancasila - Chairunnisa Depa Kartika; Camellia, Camellia (Universitas Muhammadiyah Ponorogo, 2026)
This study aims to determine the effect of Nearpod media on improving students' critical thinking skills in Pancasila Education learning at SMA Negeri 10 Palembang. The study used a quantitative approach with a quasi-experimental design involving an experimental class and a control class. The learning process in the experimental class was conducted using Nearpod media, while the control class followed conventional learning. Data were obtained through pre- and post-learning critical thinking tests and were analyzed statistically. The results showed that students' critical thinking skills improved in both classes, but the improvement in the experimental class was greater than in the control class. This finding confirms that the use of Nearpod media has a positive and more effective effect on developing students' critical thinking skills in Pancasila Education learning. Furthermore, research findings indicate that the integration of interactive learning technologies can create a more engaging learning environment, encourage critical thinking, and increase student participation in analyzing teaching materials. These findings can serve as a guide for teachers in maximizing digital-based learning methods in schools.